2022
DOI: 10.3920/jiff2021.0138
|View full text |Cite
|
Sign up to set email alerts
|

Effect of carrot supplementation on nutritional value of insects: a case study with Jamaican field cricket (Gryllus assimilis)

Abstract: The fortification of feed is known to be a useful tool to manipulate the nutritional value of insects. This study aimed to reveal the effect of carrot supplement duration on the basic nutrients, fatty acid profile, carotenes, and tocopherols. Jamaican crickets (Gryllus assimilis) were provided with chicken feed supplemented with carrots ad libitum for 0, 3, 7, 14 and 60 days prior to harvest. The supplementation increased the levels of α-carotene and β-carotene in the insects. The content of carotenoids did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…Interestingly, the levels of oleic acid in raw mealworms detected by our study were higher than those reported by other studies, such as those conducted by Wu et al (2020) or Caparros Megido et al (2018). The fatty acid profiles of Jamaican field crickets were consistent with those found in the literature, where minor differences could be attributed to different feeds, which are known to influence fatty acid composition (Kulma et al, 2021;Soares Araújo et al, 2019). Similar to that conducted by Caparros Megido et al ( 2018), our study indicated that the highest FA levels shown by raw insects, when compared to culinary processed insects, were those of two SFAs (C16:0 and C18:0) while the lowest level was that of linoleic acid The authors attributed this phenomenon to drip loss from adipose tissues containing mainly neutral lipids, such as triglycerides with relatively high SFA levels, which are more prone to migration.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Interestingly, the levels of oleic acid in raw mealworms detected by our study were higher than those reported by other studies, such as those conducted by Wu et al (2020) or Caparros Megido et al (2018). The fatty acid profiles of Jamaican field crickets were consistent with those found in the literature, where minor differences could be attributed to different feeds, which are known to influence fatty acid composition (Kulma et al, 2021;Soares Araújo et al, 2019). Similar to that conducted by Caparros Megido et al ( 2018), our study indicated that the highest FA levels shown by raw insects, when compared to culinary processed insects, were those of two SFAs (C16:0 and C18:0) while the lowest level was that of linoleic acid The authors attributed this phenomenon to drip loss from adipose tissues containing mainly neutral lipids, such as triglycerides with relatively high SFA levels, which are more prone to migration.…”
Section: Resultssupporting
confidence: 86%
“…The analysis of fatty acid composition involved the conversion of triacylglycerols into their methyl esters, followed by GC-FID analysis, using the method previously described by Kulma et al (2021). The obtained results were evaluated using the area normalisation method and subsequently expressed as relative percentages of all identified fatty acid methyl esters.…”
Section: Materials and Metodologymentioning
confidence: 99%
“…The formulated cricket feed market is constantly growing along with the increasing numbers of cricket farms in Thailand [11]. Shortly before harvest, the crickets are fed with vegetables, vegetable by-products and fruits to improve taste and nutritional profile [4,36]. Nowadays, mass production of cricket flour and cricket snacks is conducted by Thailand Unique and Smile Bull Companies, while Global Bugs is a leader in cricket flour making [11].…”
Section: Distribution Of Edible Cricketsmentioning
confidence: 99%
“…Oonincx et al [29] reported that the basic chemical composition (proteins, CF and moisture) of TM was not affected by cereal-based diets, whereas a diet enriched with unsaturated FA altered the FA profile. Additionally, the inclusion of carrot in some insect diets, such as Gryllus assimilis, did not affect the protein, lipid and ash content, but, on the contrary, it affected the FA composition [55]. Harsányi et al [30] reared insects on different organic waste and ranked garden waste as the average feed for insect larvae, vegetable waste as the poorest, and chicken feed was marked as the best.…”
Section: Proximate Compositionmentioning
confidence: 99%